Critical Thinking Skills for Dummies - Martin Cohen (UK, 2015)
Turbocharge your reasoning with Critical Thinking Just what are the ingredients of a great argument? What is the secret to communicating your ideas clearly and persuasively? And how do you see through sloppy thinking and flim-flam? If you've ever asked any of these questions, then this book is for you! These days, strong critical thinking skills provide a vital foundation for academic success, and Critical Thinking Skills For Dummies offers a clear and unintimidating introduction to what can otherwise be a pretty complex topic. Inside, you'll get hands-on, lively, and fun exercises that you can put to work today to improve your arguments and pin down key issues. With this accessible and friendly guide, you'll get plain-English instruction on how to identify other people's assumptions, methodology, and conclusions, evaluate evidence, and interpret texts effectively. You'll also find tips and guidance on reading between the lines, assessing validity - and even advice on when not to apply logic too rigidly! Critical Thinking Skills for Dummies: * Provides tools and strategies from a range of disciplines great for developing your reflective thinking skills * Offers expert guidance on sound reasoning and textual analysis * Shows precisely how to use concept mapping and brainstorming to generate insights * Demonstrates how critical thinking skills is a proven path to success as a student Whether you're undertaking reviews, planning research projects or just keen to give your brain a workout, Critical Thinking Skills For Dummies equips you with everything you need to succeed.
Keywords: Nonfiction; Philosophy